FARMERS' DECISIONS IN TUMERIC SALES IN NGEPUNG, GRESIK REGENCY - Endang Yektiningsih; Pradina Dwi Handarista; Indra Tjahaja Amir (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
Local commodity-based farming needs to be developed by improving activities upstream to downstream of agricultural industries. Turmeric is one of the local commodities in Ngepung Village, Kedamean District, Gresik Regency. This commodity, which is widely used in food and beverage, and has health benefits, has not been cultivated intensively by some farmers in the area, mainly as a secondary commodity. The lack of access to information received caused the low willingness of the farmers to develop a turmeric business. However, some farmers have worked in small to medium-scale businesses because they can produce high production. This study analyzes the factors influencing farmers' decisions to sell turmeric. The analytical method used is binary logistic regression analysis. The results indicate that the price and production have a significant effect on farmers' decisions in selling turmeric. In contrast, the variables of distance to the market, age, education, and experience in turmeric farming have no significant effect.